Open-Ended Coaxial Cable Selection for Measurement of Liquid Dielectric Properties via the Reflection Method. (6th October 2020) - Wang, Jingchen; Lim, Eng Gee; Leach, Mark Paul; Wang, Zhao; Man, Ka Lok
Abstract : An open-ended coaxial cable is used to measure the dielectric properties of lossy liquid. The method which is based on the measurement of the reflection coefficient of the open-ended cable makes it easy to operate and postprocess. To meet the accuracy requirements, the dimensions of the coaxial cable need to be taken into consideration; therefore, it is necessary to select an appropriate coaxial cable for the measurement. This paper investigates the influence of cable dimensions on dielectric measurement accuracy. With careful choice of the coaxial cable, the relative error of calculated results can be less than 0.1%.